La serie paleógena de la unidad superior del Gomáride en Talembote (Rif Interno, Marruecos) - Hlila, Rachid; Maaté, A.; Sanz de Galdeano, Carlos; Serra-Kiel, Josep; Serrano, Francisco; El Kadiri, Khalil (Sociedad Geológica de España, 2007)
43ª Sesión Científica. Móstoles, Noviembre de 2007 The lower Paleogene stratigraphic successions of the Talembote upper Ghomaride Unit represent an interval of age going from the (middle?) Ilerdian to the early Bartonian, showing a transgressive sequence interrupted by intermittent sedimentary gaps, which are indicated by surfaces of discontinuity. These sediments correspond essentially to carbonatic facies with benthic foraminifers deposited in a shallow platform that was maintained probably until the late Lutetian. The abrupt rupture of this platform allowed, during the early Bartonian, sedimentation of pelagic to hemipelagic facies in a bathyal sedimentary environment. Later, the sudden interruption of the sedimentation in the early Bartonian, indicated by a paleosoil, may be better explained by tectonic reason than eustatism taking into account many actual geodynamic reconstructions. Esta nota se ha hecho en el marco de la beca concedida a uno de los autores (R.H) por la Agencia Española de Cooperación Internacional (AECI) y del proyecto CGL 2005-00404/BTE. Peer reviewed